PENGARUH KOMPENSASI FINANSIAL, KOMPENSASI NON FINANSIAL DAN KONDISI FISIK LINGKUNGAN TERHADAP KINERJA KARYAWAN DAN DAMPAKNYA TERHADAP PENCAPAIAN TARGET PRODUKSI (Studi pada seksi Finishing, PT.Indah Kiat Pulp and Paper, Perawang Mill) - Alum Kusumah (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
The purpose of this research is to determine whether the assumption of financialcompensation, non financial compensation and physical working area have direct andsignificant impact to the employee performance in terms to achieve production target. Thisresearch was conducted by taking sample of 73 respondents. Data collected by using aquestionnaire form filled with list of questions and data analysis technique is using pathanalysis with SPSS 20.00 for Windows.The production target must be emphasizing to achieve by a management ofproduction line and can be achieve if the employee performance of Finishing section, PT.Indah Kiat Pulp and Paper, Perawang, working together to achieve the goals that havebeen settled by top management. Higher level of financial compensation, higher level ofnon financial compensation and better physical working area will also increase the level ofemployee performance to achieve production target of Finishing section, PT. Indah KiatPulp and Paper, Perawang Mill.Based on the path analysis result, it was proven that financial compensation, nonfinancial compensation and working area have direct and significant impact to theemployee performance to achieve production target to the employee of Finishing section,PT. Indah Kiat Pulp and Paper, Perawang MillKeywords: financial compensation, non financial compensation, physical working,employee performance, production target achievement